Estudio de factibilidad para la creación de un centro turístico en la comuna San Pablo, cantón Santa Elena, año 2013 - Altamirano Gonzalez, Karla Silvana (2014)
This research for the creation of a resort aims to provide the public with quality service, contributing to the development of tourism in this community, improve the quality of life of its inhabitants and meet the unmet demand by visitors of this spa. The market survey conducted by surveying residents and tourists in the district San Pablo, demonstrates the high degree of acceptance of the project, after this analysis is considered that the resort will have a great opportunity in the market as there is no other bidder on the town. The environmental impact study, identified the environmental implications, environmental record through the requirements and obligations of the investor with the environment, compliance with all rules for the implementation of this type of business was established. Analyzing the technical study, the location, size and engineering of the project to be used for the implementation of the business is determined. Beside the design of the organizational structure. The study found that for the operation of this project an investment of $ 214.397,75 is required. Net present value $ 966.256,94 proves to be greater than the initial investment. The cost-benefit result reflected us as 1.64% in the first period being greater than the investment. The internal rate of return gave 88% which shows that this project refunded twice the invested money, so we conclude that it is feasible and profitable, generating income for the investor, owner or possible partnership.